The Willow Pattern Plot - Roderick Hunt (Oxford Reading Tree, 2012)
I liked this book because it was about Biff, Chip and Kipper who used their magic key and ended up in the willow pattern garden. The girl in the story had a very angry father who forbid her from $1! =s